Technical optimization of the energy supply in geothermal heat pumps. (September 2019) - Sáez Blázquez, Cristina; Borge-Diez, David; Martín Nieto, Ignacio; Farfán Martín, Arturo; González-Aguilera, Diego
Highlights: The energy supply of geothermal heat pumps is evaluated. Electric heat pumps and gas engine heat pumps are considered. A geothermal system constituted with each heat pump model is defined in several areas. Electric heat pump system is the only scenario that respects the nZEB requirements in one area. Abstract: Very low enthalpy geothermal systems have been traditionally associated to the use of electricity as primary energy heat pumps supply. Gas engine heat pumps (GEHP) have been recently introduced in the current market. In this research, the electric heat pumps (EHP) as well as the GEHPs (considering natural gas and biogas as combustibles) have been analysed. The calculation of the ground source heat pump (GSHP) system has been made for a building placed in three different areas. Results reveal the influence of the heat pump configuration on the whole geothermal design. This research finally considers the European policies whose aim is a sustainable low-carbon economy by 2020. According to the existing Energy Efficiency Directive, energy requirements are defined for new and existing residential and non-residential buildings in the Member States. Based on these standards, the research compares the geothermal heat pump scenarios and a traditional one to determine if they would meet the regulation. Final results show that the Directive is a highly-demanding regulation that can only be respected by using EHP in one of the areas. The rest of geothermal heat pumps scenarios are much closer to meeting the energy standards than the traditional fossil heating sources.